Preparation method of large-aperture fine-aggregate porous ceramic matrix
By prefixing fine aggregates and obtaining coarse aggregates, the problem of the micropore pore size of the porous ceramic matrix decreases during the sintering process is solved, and a significantly larger micropore average pore size and smaller surface roughness are achieved, thereby improving the atomization effect.
Patent Information
- Application Number
- CN202510042645.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
During the sintering process, the microporous pore size of the existing porous ceramic matrix becomes smaller due to the shrinkage of the aggregate particles, which hinders the inhalation of the atomization liquid, resulting in a decrease in the atomization amount and blackening of the liquid carbon volume.
A two-step calcination method of pre-firing fine aggregates and obtaining coarse aggregates is used to form a dendritic skeleton structure through high-temperature pre-firing of fine aggregates and sintering aids to avoid particle shrinkage during subsequent sintering, thereby retaining micropores with larger pores.
The micropore average pore size of the porous ceramic matrix is significantly increased, making it larger than the average particle size of the fine aggregate, while maintaining a smaller surface roughness and improving the atomization effect.
Smart Images

Figure CN119822801A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of atomization cores of electronic atomization equipment, and in particular relates to a method for preparing a large-pore fine-aggregate porous ceramic matrix. Background Art
[0002] The atomizer core is the most core component of the electronic atomization device. The atomizer core includes a liquid-conducting liquid and a heating element arranged on the surface of the liquid-conducting liquid. The liquid-conducting liquid can be a porous ceramic matrix made by sintering porous ceramic materials. The interior of the liquid-conducting liquid is composed of many through-going micropores or pores. The micropores include many tiny holes and channels. These micropores and pores in the porous ceramic matrix are interconnected and interconnected, that is, they have capillary suction. The atomized liquid can be sucked into the tiny micropores and pores in the porous ceramic matrix, and then under the high-temperature heating of a heating element such as a heating wire, a heating sheet or a metal film, the atomized liquid sucked into the porous ceramic matrix can be conducted to the surface of the porous ceramic matrix, and is heated and atomized into an aerosol or smoke-like vapor that is inhaled into the user's mouth.
[0003] The pore size, pore distribution, pore penetration, porosity, and pore wall thickness of the porous ceramic matrix will greatly affect the atomization effect, such as the amount of atomization or smoke, flavor restoration, sweetness, and other taste aspects.
[0004] At present, the porous ceramic matrix is mainly prepared by a one-time sintering molding process and a method of adding a pore-forming agent. Among them, the stacking and bridging effect of the ceramic aggregate and the effect of the pore-forming agent allow a certain amount of pores to be left in the porous ceramic matrix, and the aggregates are tightly bonded together under the action of the high-temperature liquid phase of the sintering aid. However, the problem in this process is that during the sintering process, the aggregate particles will shrink during the rearrangement process at high temperature, causing the particles to be further compacted, so that the average pore size of the micropores is generally smaller than the average particle size of the aggregate particles, especially after the aggregate particle size exceeds 30um, which is more obvious, causing the large pores left by the pore-forming agent to become smaller, or even so small that the aggregate particles are densely bonded and only leave very small pores. The overly small and overly closed micropores in the porous ceramic matrix will hinder the inhalation of the atomized liquid, resulting in a reduction in the atomization amount, and even cause the micropores to be blocked, resulting in the liquid volume carbon blackening and poor taste.
[0005] In order to increase the pore size of the porous ceramic matrix, the current method is usually to use enlarged aggregate particles in the raw materials before the porous ceramic matrix is sintered. Large-diameter micropores can be formed by stacking large particles before sintering. However, the consequence is that the large particles of aggregate will cause the surface roughness of the porous ceramic matrix to increase, and the large particles will shrink and rearrange during high-temperature sintering. The pore size of the micropores will be occupied by the shrinkage of the large aggregate and become smaller. The smaller pore size leads to poor diversion of the atomized liquid, and the comprehensive performance of the liquid-conducting liquid formed by the porous ceramic matrix, such as the atomization amount and taste, is difficult to improve.
[0006] Therefore, it is necessary to find a way to make the aggregate of the porous ceramic matrix fine while the pore size of the micropores is still large and connected, so as to obtain a porous ceramic matrix with better comprehensive atomization effect. Summary of the invention
[0007] The technical problem solved by the present invention is to overcome the shortcomings of the prior art and provide a preparation method of a large-pore fine aggregate porous ceramic matrix and an atomizing core thereof.
[0008] The technical solution of the present invention is a method for preparing a porous ceramic matrix with large pore size and fine aggregate, comprising the following steps:
[0009] Obtain fine aggregate of ceramic powder, wherein the ceramic powder is at least one of kaolin, potassium feldspar, quartz, alumina, silicon carbide, cordierite, mullite, sericite, and glass sand, and the average particle size of the ceramic powder is 9-75 μm;
[0010] Obtaining a sintering aid, wherein the sintering aid is at least one of boron oxide, sodium silicate, silicon oxide, potassium oxide, lithium oxide, barium oxide, magnesium oxide, calcium oxide, iron oxide, titanium oxide, zinc oxide, and zirconium oxide;
[0011] Obtaining a pore-forming agent, wherein the pore-forming agent is at least one of graphite, starch, wood powder, flour, soybean powder, polystyrene microspheres, polymethyl methacrylate microspheres, sucrose, and fiber, and the average particle size of the pore-forming agent is 5-100 μm;
[0012] Obtaining a molding agent, wherein the molding agent is at least one of paraffin, beeswax, boric acid, oleic acid, stearic acid, polyethylene, polypropylene, polyvinyl acetate, polyvinyl acetal, ethylene-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate copolymer resin, perchlorethylene resin, polyacrylate, and polyamide;
[0013] Pre-sintering fine aggregate to obtain coarse aggregate: mixing the fine aggregate of the ceramic powder and the sintering aid, and then calcining to form a block, taking out the cooled block for ball milling, and classifying and sieving the ball-milled powder to obtain a coarse aggregate of the ceramic powder with an average particle size of 75 μm-150 μm;
[0014] Banburying and forming green body: mixing the coarse aggregate of the ceramic powder with the pore-forming agent and the forming agent, and then banburying to obtain a green body, and forming the green body into a porous ceramic green body;
[0015] Dewaxing and sintering of green body: the porous ceramic green body is dewaxed, cooled and powdered to obtain a porous ceramic body, and the porous ceramic body is sintered at high temperature to obtain a porous ceramic matrix with large pore size and fine aggregate.
[0016] Preferably, the average particle size of the ceramic powder is 9-30 μm.
[0017] Preferably, the average particle size of the pore former is 30-60 μm.
[0018] Preferably, the ball-milled powder is classified and sieved to obtain a coarse aggregate of ceramic powder with an average particle size of 100 μm-150 μm.
[0019] Preferably, in the step of pre-sintering the fine aggregate to obtain the coarse aggregate, the ratio of the fine aggregate of the ceramic powder to the sintering aid is: the fine aggregate of the ceramic powder is 60-85 parts by weight, and the sintering aid is 5-40 parts by weight.
[0020] Preferably, in the step of pre-sintering the fine aggregate to obtain the coarse aggregate, the ratio of the fine aggregate of the ceramic powder to the sintering aid is: the fine aggregate of the ceramic powder is 65-75 parts by weight, and the sintering aid is 25-35 parts by weight.
[0021] Preferably, in the steps of internal mixing and forming green bodies, the ratio of the pore-forming agent to the molding agent is: the pore-forming agent is 5-40 parts by weight, and the molding agent is 40-65 parts by weight.
[0022] Preferably, in the steps of internal mixing and forming green bodies, the ratio of the pore-forming agent to the molding agent is: the pore-forming agent is 15-30 parts by weight, and the molding agent is 40-60 parts by weight.
[0023] Preferably, in the step of pre-calcining the fine aggregate to obtain the coarse aggregate, the calcination temperature is 700-1050° C., and the calcination is kept warm for 2-10 hours.
[0024] Preferably, in the steps of dewaxing and sintering the green body, the dewaxing temperature is 300-700°C, and the sintering temperature is 700-1200°C.
[0025] Preferably, in the steps of dewaxing and sintering the green body, the dewaxing temperature is 550-700°C, and the sintering temperature is 900-1150°C.
[0026] Preferably, in the steps of mixing and forming green billets, the green billets are granulated materials or slurries, and the forming method is injection molding, die casting, or casting.
[0027] Compared with the prior art, the present invention has the following beneficial effects: the present invention adds a process of pre-sintering fine aggregate to obtain coarse aggregate, forming a two-step calcination method of aggregate pre-sintering and green body sintering, the fine aggregate is first mixed with a sintering aid and pre-sintered at high temperature, the sintering aid is melted and softened at high temperature to form a glass liquid phase, the fine aggregate is built into a dendritic skeleton structure with the help of the glass liquid phase, pre-sintered to form a block, the block is cooled and crushed, and sieved to coarse aggregate with a certain range of particle sizes, the coarse aggregate is actually agglomerated particles of fine aggregate with a dendritic skeleton structure retained, and these agglomerated particles have better stable structure. The coarse aggregate is then added with a pore-forming agent and a forming agent for mixing and kneading and forming into a green body. In this process, the accumulation of coarse aggregate can form micropores with larger pore sizes. Since the agglomerated particles of the coarse aggregate have undergone a high-temperature pre-sintering and formed a stable structure, they will not shrink again during the high-temperature sintering again, and will not occupy the micropores with larger pore sizes. The micropores with larger pore sizes can be retained after high-temperature sintering. Therefore, the average pore size of the micropores of the prepared porous ceramic is significantly increased compared to the average pore size of the micropores of the porous ceramic obtained by the first sintering, and its surface roughness will not increase because the original particle size of the fine aggregate is retained. Therefore, the preparation method of the present invention can be used to prepare a large-pore fine aggregate porous ceramic matrix, the average pore size of the internal micropores of which is significantly increased and greater than the average particle size of the fine aggregate, while maintaining a relatively small surface roughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. Unless otherwise stated, the drawings in the drawings do not constitute a scale limitation.
[0029] Figure 1 This is an enlarged view of a porous ceramic matrix with large pore size and fine aggregate prepared in Example 1 of the present invention;
[0030] Figure 2 It is an enlarged view of a common porous ceramic substrate prepared in Comparative Example 1 of the present invention;
[0031] Figure 3 This is a comparison table of pore sizes of porous ceramic substrates prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] A method for preparing a large-pore fine-aggregate porous ceramic matrix of the present invention comprises the following steps:
[0034] 1. Obtain fine aggregate of ceramic powder: Select ceramic powder to be at least one of kaolin, potassium feldspar, quartz, alumina, silicon carbide, cordierite, mullite, sericite, and glass sand, including a mixture of several of the above substances, and select ceramic powder with an average particle size of 9-75μm. Ceramic powder with an average particle size of 9-30μm is preferred. Ceramic powder with an average particle size of 15-30μm, or 30-60μm, or 60-75μm can also be selected.
[0035] 2. Obtain sintering aids: The sintering aids are selected to be at least one of boron oxide, sodium silicate, silicon oxide, potassium oxide, lithium oxide, barium oxide, magnesium oxide, calcium oxide, iron oxide, titanium oxide, zinc oxide, and zirconium oxide, including a mixture of several of the above substances.
[0036] 3. Obtain a pore-forming agent: Select a pore-forming agent that is at least one of graphite, starch, wood powder, flour, soybean powder, polystyrene microspheres, polymethyl methacrylate microspheres, sucrose, and fiber, including a mixture of several of the above substances, and select a pore-forming agent with an average particle size of 5-100 μm. A pore-forming agent with an average particle size of 30-60 μm is preferred, and a pore-forming agent with an average particle size of 60-90 μm can also be selected.
[0037] 4. Obtain a molding agent: Select a molding agent as at least one of paraffin, beeswax, boric acid, oleic acid, stearic acid, polyethylene, polypropylene, polyvinyl acetate, polyvinyl acetal, ethylene-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate copolymer resin, perchlorethylene resin, polyacrylate, and polyamide, including a mixture of several of the above substances.
[0038] 5. Pre-sintering fine aggregate to obtain coarse aggregate: the fine aggregate of the above-mentioned ceramic powder and a sintering aid are mixed and ball-milled, and then calcined to form a block, the cooled block is taken out and ball-milled, and the ball-milled powder is further graded and sieved to obtain coarse aggregate of ceramic powder with an average particle size of 75μm-150μm, preferably graded and sieved to obtain coarse aggregate of ceramic powder with an average particle size of 100μm-150μm; and graded and sieved to obtain coarse aggregate of ceramic powder with an average particle size of 80μm-120μm.
[0039] Among them, the ratio of fine aggregate and sintering aid of ceramic powder is: by weight, the fine aggregate of ceramic powder is 65-85 parts, and the sintering aid is 5-40 parts; preferably, the fine aggregate of ceramic powder is 65-75 parts, and the sintering aid is 25-35 parts; and the fine aggregate of ceramic powder can also be selected as 75-85 parts, and the sintering aid is 30-40 parts.
[0040] The calcination is carried out in a rotary kiln at a temperature of 700-1050°C, and the calcination is kept warm for 2-10 hours. The preferred calcination temperature is 800-1050°C.
[0041] 6. Mixing and forming green body: Mixing the coarse aggregate of ceramic powder with pore-forming agent and forming agent, and then mixing and forming to obtain green body, and forming the green body into porous ceramic green body;
[0042] Among them, the ratio of pore-forming agent and molding agent is: by weight, the pore-forming agent is 5-40 parts, and the molding agent is 40-65 parts; preferably, the pore-forming agent is 15-30 parts, and the molding agent is 40-60 parts; it is also possible to select pore-forming agent as 30-40 parts and molding agent as 50-65 parts.
[0043] The blank is a granulated material or a slurry, and the molding method is injection molding, die casting, or casting.
[0044] 7. Dewaxing and sintering of green body: Dewaxing the porous ceramic green body, cooling it, and removing powder to obtain a porous ceramic body, and sintering the porous ceramic body at high temperature to obtain a porous ceramic matrix with large pore size and fine aggregate;
[0045] Among them, the wax removal temperature is 300-700°C, and the sintering temperature is 700-1200°C; preferably, the wax removal temperature is 550-700°C, and the sintering temperature is 900-1150°C.
[0046] The above steps of the present invention focus on the fifth step of pre-sintering fine aggregate to obtain coarse aggregate and the seventh step of sintering green body. These two steps constitute a two-step calcination method of aggregate pre-sintering and green body sintering, that is, firstly, the fine aggregate is mixed with a sintering aid and pre-sintered at high temperature, the sintering aid is melted and softened at high temperature to form a glass liquid phase, the fine aggregate is built into a dendritic skeleton structure with the help of the glass liquid phase, pre-sintered to form a block, the block is cooled and crushed, and sieved to a coarse aggregate with a certain range of particle size, the coarse aggregate is actually agglomerated particles of fine aggregate that retains the dendritic skeleton structure, and these agglomerated particles have a relatively large The coarse aggregate is added with a pore-forming agent and a molding agent for mixing and kneading and forming into a green body. In this process, the accumulation of coarse aggregate can form micropores with larger pore sizes. Since the agglomerated particles of the coarse aggregate have undergone a high-temperature pre-sintering and formed a stable structure, they will not shrink again during the high-temperature sintering again, and will not occupy the micropores with larger pore sizes. The micropores with larger pore sizes can be retained after high-temperature sintering. Therefore, the average pore size of the prepared porous ceramic is significantly increased compared to the average pore size of the porous ceramic obtained by the first sintering, and its surface roughness will not increase because the original fine aggregate particle size is retained. Therefore, a large-pore fine aggregate porous ceramic matrix can be prepared by the preparation method of the present invention, and the average pore size of the internal micropores is significantly increased and greater than the average particle size of the fine aggregate, while maintaining a small surface roughness.
[0047] The present invention will be further described in detail below in conjunction with embodiments:
[0048] Embodiment 1
[0049] A method for preparing a large-pore fine-aggregate porous ceramic matrix of the present invention comprises the following steps:
[0050] S11, select a sufficient amount of quartz powder with an average particle size of 9 μm as fine aggregate of ceramic powder for standby use;
[0051] S12, selecting sufficient amounts of boron oxide, zirconium oxide, aluminum oxide, and calcium oxide and mixing them in a weight ratio of 1:3:4:3 as a sintering aid for later use;
[0052] S13, select a sufficient amount of polymethyl methacrylate with an average particle size of 30 μm as a pore-forming agent for standby use;
[0053] S14, select sufficient amount of paraffin, beeswax, stearic acid, and polyethylene in a weight ratio of 5:1:3:1 and mix them as a molding agent for standby use;
[0054] S15, pre-calcining fine aggregate to obtain coarse aggregate: the fine aggregate of the ceramic powder and the sintering aid are mixed in a weight ratio of 72:28 and ball-milled for 8 hours, and then calcined in a rotary kiln at a high temperature of 950° C. for 5 hours to form a block after calcination. The cooled block is taken out and ball-milled, and the ball-milled powder is graded and sieved with 100 mesh and 200 mesh sieves to select the coarse aggregate of the ceramic powder with an average particle size of 75-150 μm;
[0055] S16, mixing and forming a green body: 1000 g of the coarse aggregate of the ceramic powder, 250 g of the pore-forming agent, and 625 g of the forming agent are selected and mixed, and then mixed and granulated, and then injection molded into a porous ceramic green body;
[0056] S17, dewaxing and sintering of green body: the porous ceramic green body is buried with powder and kept at 700°C for 3 hours to dewax, and after cooling, it is cleaned and powdered to obtain a porous ceramic green body, and then the porous ceramic green body is placed in a kiln and kept at 1000°C for 6 hours for high-temperature sintering to obtain a large-pore fine-aggregate porous ceramic matrix.
[0057] As attached Figure 1 As shown in the above embodiment, the porous ceramic matrix with large pore size and fine aggregate is observed under a microscope with a magnification of 300 times. The microporous structure is shown in the attached figure. Figure 1 As shown, it is measured that the average pore size of the micropores of the porous ceramic matrix is 11-12 μm.
[0058] Comparative Example 1
[0059] D11. Select a sufficient amount of quartz powder with an average particle size of 9 μm as fine aggregate for ceramic powder and set aside;
[0060] D12, select sufficient amounts of boron oxide, zirconium oxide, aluminum oxide, and calcium oxide and mix them in a weight ratio of 1:3:4:3 as a sintering aid for later use;
[0061] D13, select a sufficient amount of polymethyl methacrylate with an average particle size of 30 μm as a pore-forming agent and set aside;
[0062] D14, select sufficient amount of paraffin wax, beeswax, stearic acid, and polyethylene in a weight ratio of 5:1:3:1 and mix them as a molding agent for later use;
[0063] D15, banburying and forming green body: 720g of the fine aggregate of the above ceramic powder, 280g of sintering aid, 250g of pore-forming agent and 625g of forming agent were selected and mixed, and then banburying and granulating were performed, and then injection molding was performed into a porous ceramic green body;
[0064] D16. Sintering to obtain a porous ceramic matrix: After burying the above-mentioned porous ceramic green body with powder, keep it at 700°C for 3 hours to remove wax, and after cooling, wash and remove powder to obtain a porous ceramic green body, and then put the porous ceramic green body into a kiln and keep it at 1000°C for 6 hours for high-temperature sintering to obtain a common porous ceramic matrix.
[0065] As attached Figure 2 As shown, the above comparative example obtained a common porous ceramic substrate, which was observed under a microscope at 300 times magnification, and its microporous structure was as shown in the attached figure. Figure 2 As shown. According to measurement, the average pore size of the micropores of the common porous ceramic matrix is 6-7 μm.
[0066] By comparing the above Example 1 with Comparative Example 1, it can be seen that under the same conditions, Example 1 adds the step of "pre-burning fine aggregate to obtain coarse aggregate", which greatly increases the average pore size of the porous ceramic matrix finally obtained.
[0067] Embodiments 2 to 5
[0068] On the basis of the above-mentioned embodiment 1, in step 1, quartz powders with average particle sizes of 15μm, 30μm, 60μm, and 75μm are selected as fine aggregates of ceramic powders, and then the same steps are repeated as embodiments 2 to 5 to obtain porous ceramic matrices with large pore size fine aggregates of different average pore sizes. According to the measurement, the average pore sizes of the micropores of the porous ceramic matrix are 18-19μm, 26-27μm, 46-48μm, and 58-60μm, respectively. Figure 3 shown.
[0069] Comparative Examples 2 to 5
[0070] Based on the above comparative example 1, in step 1, quartz powders with average particle sizes of 15 μm, 30 μm, 60 μm, and 75 μm are selected as fine aggregates of ceramic powders, and then the same steps are repeated as comparative examples 2 to 5 to obtain ordinary porous ceramic substrates with different average pore sizes. According to the measurement, the average pore sizes of the micropores of the porous ceramic substrates are 12-13 μm, 16-17 μm, 27-29 μm, and 37-39 μm, respectively. Figure 3 shown.
[0071] From the comparison between the above embodiments and the comparative examples, it can be seen that under the same conditions, embodiments 1 to 5 have added the step of "pre-burning fine aggregate to obtain coarse aggregate", so that the average pore size of the porous ceramic matrix finally obtained is much larger than that of comparative examples 1 to 5, which verifies the preparation method of the porous ceramic matrix of the present invention to prepare a micropore size larger than the average particle size of the fine aggregate while maintaining a smaller surface roughness.
[0072] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.
Claims
1. A method for preparing a porous ceramic matrix with large pore size and fine aggregate, characterized in that: The following steps are involved: Obtain fine aggregate of ceramic powder, wherein the ceramic powder is at least one of kaolin, potassium feldspar, quartz, alumina, silicon carbide, cordierite, mullite, sericite, and glass sand, and the average particle size of the ceramic powder is 9-75 μm; Obtaining a sintering aid, wherein the sintering aid is at least one of boron oxide, sodium silicate, silicon oxide, potassium oxide, lithium oxide, barium oxide, magnesium oxide, calcium oxide, iron oxide, titanium oxide, zinc oxide, and zirconium oxide; Obtaining a pore-forming agent, wherein the pore-forming agent is at least one of graphite, starch, wood powder, flour, soybean powder, polystyrene microspheres, polymethyl methacrylate microspheres, sucrose, and fiber, and the average particle size of the pore-forming agent is 5-100 μm; Obtaining a molding agent, wherein the molding agent is at least one of paraffin, beeswax, boric acid, oleic acid, stearic acid, polyethylene, polypropylene, polyvinyl acetate, polyvinyl acetal, ethylene-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate copolymer resin, perchlorethylene resin, polyacrylate, and polyamide; Pre-sintering fine aggregate to obtain coarse aggregate: mixing the fine aggregate of the ceramic powder and the sintering aid, and then calcining to form a block, taking out the cooled block for ball milling, and classifying and sieving the ball-milled powder to obtain a coarse aggregate of the ceramic powder with an average particle size of 75 μm-150 μm; Banburying and forming green body: mixing the coarse aggregate of the ceramic powder with the pore-forming agent and the forming agent, and then banburying to obtain a green body, and forming the green body into a porous ceramic green body; Dewaxing and sintering of green body: the porous ceramic green body is dewaxed, cooled and powdered to obtain a porous ceramic body, and the porous ceramic body is sintered at high temperature to obtain a porous ceramic matrix with large pore size and fine aggregate.
2. The method for preparing a large-pore fine aggregate porous ceramic matrix according to claim 1, characterized in that: The average particle size of the ceramic powder is 9-30 μm.
3. The method for preparing a large-pore fine aggregate porous ceramic matrix according to claim 1, characterized in that: The average particle size of the pore former is 30-60 μm.
4. The method for preparing a large-pore fine aggregate porous ceramic matrix according to claim 1, characterized in that: The ball-milled powder is classified and sieved to obtain a coarse aggregate of ceramic powder with an average particle size of 100 μm-150 μm.
5. The method for preparing a large-pore fine aggregate porous ceramic matrix according to claim 1, characterized in that: In the step of pre-sintering the fine aggregate to obtain the coarse aggregate, the ratio of the fine aggregate of the ceramic powder to the sintering aid is: the fine aggregate of the ceramic powder is 60-85 parts by weight, and the sintering aid is 5-40 parts by weight.
6. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the step of pre-sintering the fine aggregate to obtain the coarse aggregate, the ratio of the fine aggregate of the ceramic powder to the sintering aid is: the fine aggregate of the ceramic powder is 65-75 parts by weight, and the sintering aid is 25-35 parts by weight.
7. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the steps of internal mixing and forming green compacts, the proportion of the pore-forming agent to the molding agent is: the pore-forming agent is 5-40 parts by weight, and the molding agent is 40-65 parts by weight.
8. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the steps of mixing and preparing the green compact, the proportion of the pore-forming agent to the molding agent is: the pore-forming agent is 15-30 parts by weight, and the molding agent is 40-60 parts by weight.
9. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the step of pre-calcining the fine aggregate to obtain the coarse aggregate, the calcination temperature is 700-1050° C., and the calcination is kept warm for 2-10 hours.
10. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the steps of dewaxing and sintering the green body, the dewaxing temperature is 300-700°C, and the sintering temperature is 700-1200°C.
11. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the steps of dewaxing and sintering the green body, the dewaxing temperature is 550-700°C, and the sintering temperature is 900-1150°C.
12. The method for preparing a large-pore fine-aggregate porous ceramic matrix according to claim 1, characterized in that: In the steps of mixing and forming green billets, the green billets are granulated materials or slurries, and the forming method is injection molding, die casting, or casting.